2017
DOI: 10.1103/physreve.95.052410
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated synchronization in neuronal circuits unveiled by a phase-response-curve analysis

Abstract: Anticipated synchronization (AS) is a counter intuitive behavior that has been observed in several systems. When AS establishes in a sender-receiver configuration, the latter can predict the future dynamics of the former for certain parameter values. In particular, in neuroscience AS was proposed to explain the apparent discrepancy between information flow and time lag in the cortical activity recorded in monkeys. Despite its success, a clear understanding on the mechanisms yielding AS in neuronal circuits is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The PRC has been extensively shown to be important to explain different synchronization scenarios between coupled dynamical systems (see .e.g. [29,68]). It the case of delay-coupled neuronal populations, the PRC accurately reveals the efficacy and the direction of the information transfer.…”
Section: Role Of Collective Phase Response Functionsmentioning
confidence: 99%
“…The PRC has been extensively shown to be important to explain different synchronization scenarios between coupled dynamical systems (see .e.g. [29,68]). It the case of delay-coupled neuronal populations, the PRC accurately reveals the efficacy and the direction of the information transfer.…”
Section: Role Of Collective Phase Response Functionsmentioning
confidence: 99%
“…For example, for a specific parameter mismatch between the sender and the receiver system that gives a first-order approximation to the delayed coupling (Corron et al, 2005). AS has also been reported in a chain consisting of a sender and two receivers with switching parameters (Pyragienè and Pyragas, 2015), between two Hodgkin-Huxley neurons with different depolarization parameters (Simonov et al, 2014) and in the presence of an inhibitory loop mediated by an interneuron with a free-running frequency greater than the others (Matias et al, 2017). It has also been shown that AS may appear between two neuron models directly coupled provided that the mean frequency of the free receiver is greater than the mean frequency of the sender with (Hayashi et al, 2016) and without the explicit time-delay (Pyragienè and Pyragas, 2013; Dima et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…A common brain signature of general anesthesia is the loss of global functional connectivity between specialized regions of the cortex while local populations show increases in neural synchrony [25,34,35]. Cellular and network mechanisms leading to neural synchrony have been studied extensively in the field of computational neuroscience [36][37][38]. A set of possible network wide mechanisms are the PING (pyramidal interneuron network gamma) class of mechanisms, where stable, synchronous activity patterns emerge when inhibition periodically shuts down excitation in the network [39][40][41][42][43].…”
Section: Anesthetic Effects On Spike Synchronymentioning
confidence: 99%